Technology Entrepreneurship (ENT600) Smart wheelchair / Nik Amirul Khalid Nik Dziauddin, Mohamad Noor Ariffin Mohamad Khalid and Mohamad Noor Ariffin Mohamad Khalid. - Nik Dziauddin, Nik Amirul Khalid; Mohamad Khalid, Mohamad Noor Ariffin; Mohd Kamal, Muhammad Ikmal Naim
As students from UiTM Shah Alam, we need to complete the New Product Development assignment to fulfill the ENT600 course. We need to come up with a new innovation that can be done on existing product or a new invention that can benefit the society and do well in the market. Hence, we came up with smart wheelchair that acts as an innovation to the existing wheelchair. Hence, certain research and development are done to get a few ideas that can be implemented on the smart wheelchair. After all ideas are list down, the screening of ideas is done to identify which ideas are implementable. The product is sketched to get the visual of the ideas. Our target market is mainly the hospital where wheelchair is commonly used. The wheelchair user there is a sample of population that is use in our market testing. We also target to commercialize the product at the old folks home, rehabilitations centre and home if the product is viable.